Issues on legal knowledge bases traceability - Paliulionienė, Laima; Čaplinskas, Albertas (Lietuvos matematikos rinkinys, 2007)
Requirements traceability is used in many disciplines including system and software engineering. Usually traces are used to describe and follow the life of a requirement, in both a forward and backward directions. Traceability problems are faced in legal knowledge bases, too. However, in this case legal statements should be traced instead of requirements. Traces required to trace legal statements are specific in many aspects, therefore requirements tracing methods cannot be applied directly. The paper discusses the problems of traceability in legal knowledge bases and investigates the applicability of traceability matrices to solve these problems.